SOSIALISASI PENANGANAN CEDERA OLAHRAGA TINGKAT SD SE- KECAMATAN PRAYA TENGAH KABUPATEN LOMBOK TENGAH NTB - Herlina, Herlina; Burhan, Zakir; Hasan Ashari, L (LPPM Institut Pendidikan Nusantara Global, 2022)
The training in injury handling or what is called Sports Injury is very important to do especially for sports teachers at the Elementary, Junior, High School, and coach levels. Moreover, physical education lecturers at Institut Pendidikan Nusantara Global holdtraining for the community to expand and increase the knowledge of sports players. By doing so, they can further explore the handling of injuries to students and even athletes when competing so that athletes who experience injuries or dislocations when competing compete more quickly handled.